Ionic liquid pre-intercalated MXene films for ionogel-based flexible micro-supercapacitors with high volumetric energy density - Nicolosi, Valeria; Bao, Xinhe; Zheng, Shuanghao; Zhang, Chuanfang (John); Zhou, Feng; Dong, Yanfeng; Shi, Xiaoyu; Wu, Zhong-Shuai (My University, 2019)
MXenes are emerging as a very promising electrode material of high-performance micro-supercapacitors (MSCs) for microscale electronics. However, MXene based MSCs (M-MSCs) reported so far exhibit low areal (≤10 μW h cm−2) and volumetric (≤20 mW h cm−3) energy densities due to their narrow working voltage in aqueous systems (0.6–1.0 V). Herein, we report for the first time the construction of high-voltage and high-energy flexible ionogel-based M-MSCs with interdigital microelectrodes of ionic liquid pre-intercalated MXene films. Benefitting from the pre-intercalation of ionic liquid, the as-fabricated M-MSCs, working at 3 V in 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4), exhibited high areal and volumetric energy densities of 13.9 μW h cm−2 and 43.7 mW h cm−3, respectively, both of which are among the highest values for the reported M-MSCs. Moreover, all-solid-state M-MSCs using ionogel electrolytes displayed exceptional flexibility without capacitance loss under various deformation conditions and seamless integration free of metal-based interconnections for boosting voltage output. Therefore, such high-energy M-MSCs hold great potential for direct integration of flexible and miniature electronics.
PUBLISHED
Keywords: MXenes; Capacitance; Electrochemical electrodes; Flexible electronics; Ionic liquids; Microelectrodes; Supercapacitor